PERFORMANCE AND INTERNAL CONTROL - Sri Mifti; Nugroho Budi Lestariyo; Anacostia Kowanda (Universitas Gunadarma, 2009)
The objective of this study is to measure the influence of internal auditing on performance. Research object is Inspectorate General Department of Home Affairs staffs. As research instrument, questionnaire was developed and distributed to respondents. Closed type questionnaire was developed with five (5) choices to measure the two (2) research variables. Internal auditing is measured using six (6) dimensions, and performance is measured using three (3) dimensions. As the two variables are latent in nature, then path diagram was used to process data. Result indicates that internal auditing influence performance significantly.Keywords : internal auditing, performance, inspectorate general, home affairs